Effect of soil solarization on soil microflora with special reference to Dematophora necatrix in apple nurseries - S.K. SHARMA, MAMTA SHARMA and (Indian Phytopathology, 2002)
Soil solarization with transparent polyethylene sheets (25 and 50 mm) increased the soil temperature more than 10 and Gec at 10 and 30 cm depths, respectively as compared to unsolarized soils. The pathogen (Dematophora necatrix) was killed upto 30 cm depth in solarized soils, however, in unsolarized soils it remained viable at a" the depths. The population of antagonistic microorganisms increased after solarization, however, total microbial population including fungi, bacteria and actinomycetes decreased. Reduction in microbial population was maximum at 10 cm depth followed by 20 and 30 cm depths under both the tarps. Chemical characteristics of soil such as available nitrogen, potassium, organic carbon contents, electrical conductivity and pH increased after solarization, however, the phosphorus content decreased. Solarization also eliminated the weed population which otherwise would have helped in survival and dispersal of the pathogen.